2006
DOI: 10.1128/jcm.00312-06
|View full text |Cite|
|
Sign up to set email alerts
|

Culture-Independent Analyses of Temporal Variation of the Dominant Fecal Microbiota and Targeted Bacterial Subgroups in Crohn's Disease

Abstract: Gut microbiota shows host-specific diversity and temporal stability and significantly contributes to maintenance of a healthy gut. However, in inflammatory bowel disease, this microbiota has been implicated as a contributory factor to the illness. This study compared bacterial dynamics in Crohn's disease patients to those in a control group using a culture-independent method to assess the temporal stability, relative diversity, and similarity of the dominant fecal microbiota, Clostridium spp., Bacteroides spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
159
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(175 citation statements)
references
References 70 publications
11
159
2
1
Order By: Relevance
“…This difference was largely due to lower relative abundances of B. uniformis and higher abundances of B. ovatus and B. vulgatus, in patients with ileal involvement compared with both healthy twins and twins with colonic disease. Several previous reports have also shown an abnormal Bacteroides community in CD patients compared to healthy individuals (Seksik et al, 2003;Ott et al, 2004;Scanlan et al, 2006). For example, Scanlan et al (2006) reported a lower complexity of DGGE (denaturing gradient gel electrophoresis) profiles within the B. fragilis subgroup in CD patients than in healthy individuals and a difficulty in obtaining PCR products from CD patients compared to controls.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This difference was largely due to lower relative abundances of B. uniformis and higher abundances of B. ovatus and B. vulgatus, in patients with ileal involvement compared with both healthy twins and twins with colonic disease. Several previous reports have also shown an abnormal Bacteroides community in CD patients compared to healthy individuals (Seksik et al, 2003;Ott et al, 2004;Scanlan et al, 2006). For example, Scanlan et al (2006) reported a lower complexity of DGGE (denaturing gradient gel electrophoresis) profiles within the B. fragilis subgroup in CD patients than in healthy individuals and a difficulty in obtaining PCR products from CD patients compared to controls.…”
Section: Discussionmentioning
confidence: 97%
“…Several previous reports have also shown an abnormal Bacteroides community in CD patients compared to healthy individuals (Seksik et al, 2003;Ott et al, 2004;Scanlan et al, 2006). For example, Scanlan et al (2006) reported a lower complexity of DGGE (denaturing gradient gel electrophoresis) profiles within the B. fragilis subgroup in CD patients than in healthy individuals and a difficulty in obtaining PCR products from CD patients compared to controls. In this study, it was not problematic to obtain PCR products for the Bacteroides group, which could simply reflect differences in Bacteroides abundances within the sample groups of the two studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, recent studies demonstrate that obesity in humans and ob/ob mice is associated with stereotypical imbalances in the normal gut microbiota (31)(32)(33). Likewise, previous studies of human IBD, using standard culture techniques (34)(35)(36) or molecular analysis (37)(38)(39)(40)(41)(42)(43), have noted alterations in the GI microbiota. However, most of these IBD studies have been limited in statistical power and precision of identification or have examined only the fecal microbiota, which differs substantially from that of the GI mucosa (44).…”
mentioning
confidence: 99%